2006
DOI: 10.1158/1078-0432.ccr-05-1700
|View full text |Cite
|
Sign up to set email alerts
|

p8 Is a New Target of Gemcitabine in Pancreatic Cancer Cells

Abstract: Gemcitabine is the only available chemotherapeutic treatment of pancreatic cancers. It is, however, moderately effective, showing a tumor response rate of only 12%. The aim of this work was to identify new pathways involved in the resistance of pancreatic cancer cells to gemcitabine, in the hope of developing new adjuvant strategies to enhance its therapeutic efficacy. Comparison of gene expression patterns of five human pancreatic cancer cell lines showing different degrees of resistance to gemcitabine reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 30 publications
2
85
0
Order By: Relevance
“…Precise mechanisms for pancreatic cancer cell resistance to gemcitabine are not well understood, and gene expression profiles in correlation with cell sensitivity have been proposed. These multiple genes encode for proteins involved both in the regulation of survival or apoptotic machinery, including Src tyrosine kinase (29), c-Met tyrosine kinase receptor (30), protein kinase B/ Akt and NF-κB (31), focal adhesion kinase (32), integrinlinked kinase (33), inhibitor of apoptosis proteins (34), antiapoptotic Bcl-2 or Bcl-xL (35), and p8 proteins (36), or in phenotypic alterations including epithelial-to-mesenchymal transition and reexpression of stem cell markers (30). Nucleoside transporters, including hENT1, and cellular enzymes, including dCK, RRM1, and RRM2, which regulate gemcitabine transport and metabolism, respectively, are also important determinants for gemcitabine cytotoxicity and clinical efficacy in pancreatic cancer (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Precise mechanisms for pancreatic cancer cell resistance to gemcitabine are not well understood, and gene expression profiles in correlation with cell sensitivity have been proposed. These multiple genes encode for proteins involved both in the regulation of survival or apoptotic machinery, including Src tyrosine kinase (29), c-Met tyrosine kinase receptor (30), protein kinase B/ Akt and NF-κB (31), focal adhesion kinase (32), integrinlinked kinase (33), inhibitor of apoptosis proteins (34), antiapoptotic Bcl-2 or Bcl-xL (35), and p8 proteins (36), or in phenotypic alterations including epithelial-to-mesenchymal transition and reexpression of stem cell markers (30). Nucleoside transporters, including hENT1, and cellular enzymes, including dCK, RRM1, and RRM2, which regulate gemcitabine transport and metabolism, respectively, are also important determinants for gemcitabine cytotoxicity and clinical efficacy in pancreatic cancer (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…9 P8 participates in a wide range of biological functions in tumorigenesis, including anti-inflammatory, 10 cell cycle regulation, 11 autophagy, 12 and apoptosis inhibition. 13 Accumulating studies have shown that p8 is overexpressed in various cancer cells including pancreatic cancer, 14 colorectal carcinoma 15 and brain tumors. 16 Moreover, it has been reported that p8 is involved in the resistance of cancer cells to gemcitabine and adriamycin.…”
Section: Introductionmentioning
confidence: 99%
“…16 Moreover, it has been reported that p8 is involved in the resistance of cancer cells to gemcitabine and adriamycin. 14,17 Therefore, p8 might be a new drug-targetable gene in preventing the progression and metastasis of cancer. 18 In this study, we discovered DHA upregulates p8 remarkably in several cancer cells, and we sought to find out what role p8 plays in the antiproliferative actions of DHA in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…whether it is stimulating or inhibiting may vary in different malignancies. COM1 has been found to aid the establishment of metastasis and to play a key role in the progression of malignancies of breast (1,(5)(6)(7)13), thyroid (4,13,14), central nervous system (15) and pancreas (3,16,17). COM1 has been implicated in inducing chemoresistance in pancreatic and breast cancer cells, protecting them from apoptosis and making tumour cells genetically unstable (17).…”
Section: Discussionmentioning
confidence: 99%